PENERAPAN APLIKASI ACCURATE ACCOUNTING 4 ENTERPRISE DALAM PENYUSUNAN LAPORAN KEUANGAN PADA KUBE BATIK SRIKANDI KEKI BERDASARKAN SAK EMKM - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2023)
KUBE Batik Srikandi Keki is a Micro, Small and Medium Enterprises (UMKM) having its address at Kemiri Kidul Village, RT 02, RW 03, Kemiri District, Purworejo Regency. Accounting records at KUBE Batik Srikandi Keki are still very simple and manual, not computerized yet. This study aims to apply the Accurate Accounting 4 Enterprise application as a tool in preparing financial reports at KUBE Batik Srikandi Keki. The method used in this study uses qualitative and quantitative data. Data collection techniques by means of interviews, observation, documentation, and literature study. The researcher applies the Accurate Accounting 4 Enterprise application in preparing the financial statements of KUBE Batik Srikandi Keki. The reports produced are statements of financial position, profit and loss statements, notes to financial statements as of January 31, 2021 in accordance with the principles of SAK EMKM. The results of this study indicate that the Accurate Accounting 4 Enterprise application can be applied to the operational cycle of KUBE Batik Srikandi Keki. This application is very helpful in preparing the financial statements of KUBE Batik Srikandi Keki because the initial balance input is only when using the application for the first time while the initial balance for the next period is generated by the application. Each transaction input is automatically entered into the activity ledger and inventory card. Financial reports generated from this application are more accurate and valid.